Answer:
£7
Step-by-step explanation:
Let's call Josh's money 'J' and Leon's money 'L'.
Then, we can write the following system of equations:
[tex]J + L = 73[/tex]
[tex](J - 5) = 1.25(L - 5)[/tex]
From the first equation, we have:
[tex]J = 73 - L[/tex]
Using this value of 'J' in the second equation, we have:
[tex](73 - L - 5) = 1.25(L - 5)[/tex]
[tex]68 - L = 1.25L - 6.25[/tex]
[tex]2.25L = 74.25[/tex]
[tex]L = 33[/tex]
[tex]J = 73 - L = 73 - 33 = 40[/tex]
At the start Josh has £40 and Leon has £33, so the difference is:
[tex]J - L = 40 - 33 = 7[/tex]